DESAIN DAN IMPLEMENTASI SISTEM BANTU BLIND SPOT MENGGUNAKAN SENSOR ULTRASONIK, PIR, LDR, DAN IMU PADA KENDARAAN BERAT - Eduart Hotman Purba; Jerryo Daniel Saragih; Rio Rivaldo Sinurat; Eka Dodi Suryanto; Dian Putra Saragi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Accidents involving large vehicles such as trucks are often caused by blind spots that restrict the driver’s view. This research aims to develop a mictocontroller-based blind spot detection system capable of detecting objects, distinguishing between humans and inanimate objects, and adjusting detection system capable of detecting objects, distinguishing between humans and inanimate objects, and adjusting detection sensitivity according to environmental conditions. This system uses an Arduino Uno as the main controller, integrated with two ultrasonic sensors to detect the distance of objects in front and behind the vehicle. The Passive Infrared (PIR) sensor detects the presence of humans based on body heat radiation, while the Light Dependent Resistor (LDR) sensor sets the detection threshold to 30 cm in bright conditions and 50 cm in dark conditions. The Inertial Measurement Unit (IMU) sensor makes the system active only when the vehicle is moving, thus saving power. The results show that the system detects objects with high accuracy within the specified distance range, correctly distinguishes humans, and responds well to changes in light and vehicle movement. This system is expected to be an effective solution to improve driving safety in large vehicles through early warning in blind spot areas.